Optimization of the REJAFA information system to improve document filing for lecturer functional positions - Wildani Eko Nugroho; Very Kurnia Bakti; Ghea Dwi Rahmadiane; Sigit Ardianto (Universitas Muhammadiyah Magelang, 2021)
Functional positions or academic positions of lecturers are positions that indicate the duties, responsibilities, authorities and rights of a person in higher education which in its implementation is based on certain independent skills. The collection of lecturers' functional position files before the existence of this system was still done manually, by collecting files or portfolios in hard files and sent to LLDikti 6. This administrative aspect is one of the barriers for lecturers in improving competence. There are also a number of lecturers who do not yet have the ability to implement information technology related to the collection of functional position files. This community service was carried out with a webinar, which discussed the use of information technology called REJAFA (repository jabatan fungsional). The results of the community service were quite interactive and the enthusiasm of the participants was quite good because the main discussion was related to optimizing the REJAFA system to improve document filing for the functional positions of lecturers.